Waste glass fine aggregate based on modification of composite modifier and preparation method of waste glass fine aggregate
By pretreating and modifying the waste glass, combined with the use of composite modifiers, the problem of low recycling rate of waste glass is solved, and efficient preparation of fine aggregates of waste glass and improvement of concrete performance is achieved.
Patent Information
- Application Number
- CN202411610700.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, there are many types of waste glass color, and the sorting and processing technology and equipment are incomplete, resulting in a low recycling rate of waste glass.
Using a preparation method based on composite modifier, a glass powder is prepared by pretreating the waste glass, and the metakaolin modified is combined with diethanolamine, lithium carbonate, etc. to form a composite modifier, and mixed it in cement and glass powder to form a modified waste glass fine aggregate.
It improves the utilization rate of waste glass, inhibits the alkali-silicon expansion reaction, avoids concrete cracking, increases the age strength of cement, and improves the performance of gelled materials.
Smart Images

Figure BDA0005130836420000061 
Figure BDA0005130836420000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new material preparation, and in particular to waste glass fine aggregate based on a composite modifier and a preparation method thereof. Background Art
[0002] At present, construction waste is mixed with used glass containers, glass bulbs and other waste glass. A large amount of waste glass is abandoned, which not only occupies land, but also pollutes the environment and causes waste of resources and energy. In view of the existing domestic technology, it is currently generally adopted to recycle waste glass into furnaces for remaking and processing new glass fiber products and other materials. However, before use, it is necessary to sort the glass according to its color, and remove impurities such as labels, adhesives and residues in the container on the glass, resulting in complicated preliminary processing steps for waste glass. In addition, the lack of awareness of renewable resources among the people has led to the recycling and reuse of waste glass at only 25% to 30%. Summary of the invention
[0003] The purpose of the present invention is to achieve full utilization of waste glass and solve the problem that the existing waste glass has many colors and varieties, and the sorting and processing technology and equipment are not perfect, resulting in a low recycling rate of waste glass.
[0004] In order to achieve the above object, the present invention provides a method for preparing waste glass fine aggregate based on composite modifier modification, comprising the following steps:
[0005] S1, pre-treating waste glass to produce glass powder;
[0006] S2, drying the metakaolin, adding an amino silane coupling agent and ball milling to obtain modified metakaolin; the mass ratio of the amino silane coupling agent to the metakaolin is (1-3):100;
[0007] S3, selecting 4-6 parts of the modified metakaolin prepared in S2, 0.1-0.3 parts of lithium carbonate, and 0.4-0.6 parts of diethanolamine and mixing them to obtain a composite modifier;
[0008] S4, adding 400-500 parts of standard cement, 1350-1450 parts of the glass powder, and all the composite modifiers prepared in S3 into 200-250 parts of water, and mixing and stirring to prepare waste glass fine aggregate modified by the composite modifier; the parts are all parts by mass.
[0009] Wherein, step S1 comprises:
[0010] S1.1, after collecting the waste glass slag from construction, screen and separate it; firstly, wash the sand and mud out of the waste glass slag by water, then separate the metal material by magnetic field, and finally screen to obtain only the glass slag;
[0011] S1.2, grinding the glass slag obtained in S1.1 into glass powder.
[0012] Preferably, the specific surface area of the glass powder is 200 to 500 m 2 / g. If the specific surface area of glass powder is too large, it is easy to absorb other materials and affect the working performance of aggregate.
[0013] Preferably, the amino silane coupling agent is KH550.
[0014] Preferably, the mass ratio of KH550 to metakaolin is 2:100.
[0015] The present invention also discloses a waste glass fine aggregate prepared by the above method, characterized in that it is formed by mixing 4 to 6 parts of modified metakaolin, 0.1 to 0.3 parts of lithium carbonate, 0.4 to 0.6 parts of diethanolamine, 200 to 250 parts of water, 400 to 500 parts of standard cement and 1350 to 1450 parts of glass powder; the above parts are all parts by mass.
[0016] The beneficial effects of the present invention include: modifying metakaolin by KH550 so that it is easier to disperse and the utilization rate of metakaolin is improved; using modified metakaolin as an admixture in cement mortar containing waste glass can effectively inhibit alkali-silicon expansion reaction and avoid concrete cracking as much as possible; using diethanolamine and lithium carbonate as active stimulants and the synergistic effect of modified metakaolin, diethanolamine and lithium carbonate can increase the age strength of cement. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In order to achieve full utilization of waste glass, the problem that existing waste glass has many colors and varieties, and the sorting and processing technology and equipment are still imperfect, resulting in a low recycling rate of waste glass. The present invention discloses a method for preparing waste glass fine aggregate based on a composite modifier, which is mainly suitable for the recycling of waste glass slag. By analyzing the chemical and physical components of waste glass, it is not necessary to perform too high a treatment on the waste glass when it is used as a building material. A large amount of cement is used in engineering construction. The waste glass is ground into particles of different particle sizes and used as fine aggregate instead of sand. By adding a composite modifier (modified kaolin, diethanolamine, lithium carbonate), the amount of sand can be saved and the replacement of fine aggregate can be achieved. It can not only improve the performance of cementitious materials, but also achieve high returns in green and environmental protection.
[0019] The present invention discloses a method for preparing waste glass fine aggregate based on composite modifier modification, comprising the following steps:
[0020] S1, pre-processing of waste glass, including:
[0021] S1.1 After collecting the waste glass slag from construction, it is screened and separated; firstly, sand, soil, mud and other materials are washed out from the waste glass slag by water, then the metal materials such as steel bars are separated by magnetic field, and finally, only the glass slag is obtained by precise screening;
[0022] S1.2 The glass powder obtained in S1.1 is ground into glass powder, and glass powders with different specific surface areas can be prepared as needed; the glass powder is an irregular hard material with the characteristics of easy polishing, high transparency, controllable particle size, and anti-slip.
[0023] S2, drying the metakaolin, adding an amino silane coupling agent and performing ball milling to obtain modified metakaolin.
[0024] Kaolin is a mineral admixture with a super strong volcanic ash effect. Kaolin contains a large amount of amorphous SiO2 and Al2O3. These active substances can participate in the secondary hydration reaction in large quantities and improve the mechanical properties of concrete. Studies have shown that the compressive strength of kaolin increases significantly with the increase of the dosage, but excessive dosage of kaolin will seriously affect the working performance of concrete. Therefore, when using glass powder instead of sand, kaolin can be used as an admixture to improve the secondary hydration reaction of glass powder. Since kaolin has a high specific surface area (≥2300m 2 / kg) and layered structure, which has strong water absorption and the layered structure is not conducive to the relative movement between particles, resulting in poor concrete working performance, thus affecting the pumpability and filling capacity of concrete, and ultimately affecting the later performance of concrete. Metakaolin has a high fineness, which makes it easy to agglomerate and difficult to disperse, which is not conducive to the active effect of metakaolin. The modified metakaolin will produce a large number of hydroxyl groups during the cement hydration process. The polycondensation reaction products in an alkaline environment will combine on the surface of the particles to form a steric hindrance effect. In cement mortar containing waste glass, it can effectively inhibit the alkali-silicon expansion reaction and prevent concrete cracking. The negative charge effect of the coupling agent causes electrostatic repulsion between particles. The combined effect of the two significantly improves the rheological properties of cement-based materials.
[0025] S3, according to the same mass parts, select 4-6 parts of modified metakaolin prepared in S2, 0.1-0.3 parts of lithium carbonate, and 0.4-0.6 parts of diethanolamine and mix them to obtain a composite modifier. Diethanolamine and lithium carbonate can be used as activators to increase the age strength of cement. The activator is an active substance that can activate glass powder and is a composite agent that allows it to undergo a chemical reaction. Industrial waste slag contains a large amount of active substances such as SiO2 and Al2O3, but they exist in an inert state of "vitreous body". By activating chemical methods, they can react chemically and produce connectivity, which can greatly reduce the amount of cement and improve its utilization rate. Waste glass has similar properties to fly ash after being ground into powder. And glass exists in an amorphous structure, which is rich in calcium and silicon elements. The smaller the particle size of the waste glass powder obtained by ball milling, the higher the temperature, and the more obvious this similar property. Therefore, when glass powder is used as aggregate to participate in the reaction, adding an activator can not only effectively improve the activity of glass powder, but also reduce the use of sand.
[0026] S4, add 400-500 parts of reference cement, 1350-1450 parts of glass powder, and all the composite modifiers prepared in S3 to 200-250 parts of water, mix and stir. The reference cement is a Portland cement with a strength grade greater than 42.5 made by grinding Portland cement clinker tricalcium silicate, dicalcium silicate, tricalcium aluminate, tetracalcium aluminoferrite, and gypsum, without any admixture.
[0027] The invention is described below with reference to specific embodiments and comparative examples.
[0028] Example 1
[0029] S1, pre-treating the waste glass, i.e., screening and separating the glass slag and grinding it to obtain glass powder, the specific surface area of which is 250m 2 / g, and the glass powder was marked as A.
[0030] S2, after drying the metakaolin, KH550 is added for ball milling to obtain modified metakaolin.
[0031] S3, select 4 g of the modified metakaolin prepared in S2, 0.1 g of lithium carbonate, and 0.4 g of diethanolamine, and mix them to obtain a composite modifier.
[0032] S4, add 450g of reference cement, 1350g of glass powder, and all the composite modifiers prepared in S3 to 225g of water, mix and stir, and prepare waste glass fine aggregate modified by composite modifier. According to the cement mortar strength test method (ISO method) in the "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG E30-2005), first add water to the container, and then add cement, glass powder, and composite modifier. Stir at low speed for 60s, then stir at high speed for 30s, and stop stirring for 90s. Within the first 15 seconds of stopping stirring, scrape the blade and mortar on the container wall into the pot, and then continue stirring at high speed for 60s.
[0033] Example 2
[0034] S1 and S2 are the same as those in Example 1.
[0035] S3, select 5 g of the modified metakaolin prepared in S2, 0.2 g of lithium carbonate, and 0.5 g of diethanolamine, and mix them to obtain a composite modifier.
[0036] S4, adding 450 g of standard cement, 1400 g of glass powder, and all the composite modifiers prepared in S3 into 225 g of water, mixing and stirring.
[0037] Example 3
[0038] S1 and S2 are the same as those in Example 1.
[0039] S3, select 6 g of the modified metakaolin prepared in S2, 0.3 g of lithium carbonate, and 0.6 g of diethanolamine, and mix them to obtain a composite modifier.
[0040] S4, add 450 g of base cement, 1450 g of glass powder, and all the composite modifiers prepared in S3 into 225 g of water, mix and stir.
[0041] Comparative Example 1
[0042] 450 g of standard cement and 1350 g of sand were added to 225 g of water, and the mixture was stirred to prepare aggregate.
[0043] Comparative Example 2
[0044] S1 is the same as Example 1, without step S2 for preparing modified metakaolin.
[0045] S3, select 0.2 g of lithium carbonate and 0.5 g of diethanolamine and mix them to obtain a composite modifier.
[0046] S4, add 450 g of base cement, 1450 g of glass powder, and all the composite modifiers prepared in S3 into 225 g of water, mix and stir.
[0047] Comparative Example 3
[0048] S1 and S2 are the same as those in Example 1.
[0049] S3, select 5 g of the modified metakaolin prepared in S2 and mix with 0.5 g of diethanolamine to obtain a composite modifier.
[0050] S4, add 450 g of base cement, 1450 g of glass powder, and all the composite modifiers prepared in S3 into 225 g of water, mix and stir.
[0051] Comparative Example 4
[0052] S1 and S2 are the same as those in Example 1.
[0053] S3, select 5 g of the modified metakaolin prepared in S2 and 0.2 g of lithium carbonate and mix them to obtain a composite modifier.
[0054] S4, adding 450 g of standard cement, 1400 g of glass powder, and all the composite modifiers prepared in S3 into 225 g of water, mixing and stirring.
[0055] The aggregate prepared by modifying the A-type glass powder is recorded as the A-type test block. The raw material ratios of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 1, and the compressive strength and flexural strength of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 2.
[0056] Table 1 Type A test block ratio table
[0057]
[0058] Table 2 Compressive strength and flexural strength parameters of type A test blocks
[0059] Group Compressive strength(Mpa) Flexural strength(Mpa) Comparative Example 1 46.0 7.0 Example 1 47.5 7.5 Example 2 49.3 8.2 Example 3 46.8 6.8 Comparative Example 2 45.7 6.2 Comparative Example 3 46.3 5.4 Comparative Example 4 45.5 5.8
[0060] As shown in Table 1 and Table 2, it is found through the above examples and comparative examples that the compressive strength and flexural strength of the test block after adding metakaolin, ethylene glycol amine and lithium carbonate are significantly increased. When the added metakaolin is 5g, ethylene glycol amine is 0.2g, and lithium carbonate is 0.5g, the compressive and flexural strengths of the test block are the best. That is, the specific surface area of type A is 250m 2 The optimal ratio of metakaolin, ethylene glycol amine and lithium carbonate for / g of glass powder is 5:0.2:0.5, denoted as SA.
[0061] Comparative Examples 2 to 4 show that when any one of the three is missing, the compressive and flexural strengths of the test blocks are lower than those of Examples 1 to 3 and Comparative Example 1, and the best effect of the three being present at the same time cannot be achieved, indicating that modified metakaolin, lithium carbonate, and ethylene glycolamine are indispensable.
[0062] Based on Example 2, B (specific surface area of 310 m 2 / g), C (specific surface area 420m 2 / g) two different types of glass powder were used for ratio experiment. Glass powders with different specific surface areas have different requirements for the dosage of metakaolin, ethylene glycol amine and lithium carbonate. The experiment was continued to verify the optimal ratio of the composite modifier for the two types of glass powders B and C, as shown in Table 3.
[0063] Table 3 Optimal ratio of composite modifiers corresponding to glass powders with different specific surface areas A, B, and C
[0064]
[0065] The best ratio of metakaolin, ethylene glycol amine and lithium carbonate for type B glass powder is 4:0.1:0.4, denoted as SB; the best ratio of metakaolin, ethylene glycol amine and lithium carbonate for type C glass powder is 6:0.3:0.6, denoted as SC. If the specific surface area of the glass powder is too large, it is easy to absorb other materials and affect the working performance of the aggregate.
[0066] In summary, the present invention provides a waste glass fine aggregate modified by a composite modifier and a preparation method thereof. The metakaolin is modified by KH550 to make it easier to disperse, thereby improving the utilization rate of the metakaolin. The modified metakaolin is used as an admixture in cement mortar containing waste glass to effectively inhibit the alkali-silicon expansion reaction and avoid concrete cracking as much as possible. Diethanolamine and lithium carbonate are used as active stimulants, and the synergistic effect of the modified metakaolin, diethanolamine and lithium carbonate can increase the age strength of cement.
[0067] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing waste glass fine aggregate modified by a composite modifier, characterized in that: The following steps are involved: S1, pre-treating waste glass to produce glass powder; S2, drying the metakaolin, adding an amino silane coupling agent and ball milling to obtain modified metakaolin; the mass ratio of the amino silane coupling agent to the metakaolin is (1-3):100; S3, selecting 4-6 parts of the modified metakaolin prepared in S2, 0.1-0.3 parts of lithium carbonate, and 0.4-0.6 parts of diethanolamine and mixing them to obtain a composite modifier; S4, adding 400-500 parts of standard cement, 1350-1450 parts of the glass powder, and all the composite modifiers prepared in S3 into 200-250 parts of water, and mixing and stirring to prepare waste glass fine aggregate modified by the composite modifier; The parts mentioned are all parts by mass.
2. The preparation method according to claim 1, characterized in that Step S1 comprises: S1.1, after collecting the waste glass slag from construction, screen and separate it; firstly, wash the sand and mud out of the waste glass slag by water, then separate the metal material by magnetic field, and finally screen to obtain only the glass slag; S1.2, grinding the glass slag obtained in S1.1 into glass powder.
3. The preparation method according to claim 1, characterized in that: The specific surface area of the glass powder is 200 to 500 m 2 / g.
4. The preparation method according to claim 1, characterized in that: The amino silane coupling agent is KH550.
5. The preparation method according to claim 4, characterized in that: The mass ratio of KH550 to metakaolin is 2:
100.
6. A waste glass fine aggregate prepared by the method according to any one of claims 1 to 5, characterized in that: 4-6 parts of modified metakaolin, 0.1-0.3 parts of lithium carbonate, 0.4-0.6 parts of diethanolamine, 200-250 parts of water, 400-500 parts of standard cement and 1350-1450 parts of glass powder are mixed to form the mixture; the parts are all parts by mass.